Effect of seeding rate on seed production of perennial ryegrass after establishment with a grain companion crop in the Peace River region of north-western Canada - Fairey, N. A.; Lefkovitch, L. P. (Canadian Journal of Plant Science, 2001)
A field study in the Peace River region of north-western Canada evaluated the effect of seeding rate on the seed yield and quality of perennial ryegrass (Lolium perenne L.) in the year after establishment with a grain companion crop. Each of two sites was sown with 70 kg ha –1 barley (Hordeum vulgare L.) and under-sown, in 30-cm rows, with three cultivars (All*Star, Barclay and Repell) of diploid perennial ryegrass at seeding rates of 150, 300, 600, 1200, 2400 and 4800 viable seeds m –2 . During the establishment year of the perennial ryegrass, the grain yield of the barley companion crop was comparable to commercial yields for the region. Time of seed maturity, seed yield and thousand-seed weight of perennial ryegrass were not significantly (P ≤ 0.05) affected by the seeding rate, but were by cultivar. There was a significant (P ≤ 0.01) seeding rate × cultivar interaction for fertile tiller density and specific seed weight. Seed dockage differed significantly (P ≤ 0.001) among cultivars (16.7–27.9%) and increased with seeding rate (19.8–24.2%), and the germination capacity of the harvested seed was unaffected by seeding rate or cultivar. Grass seed yield was positively associated with fertile tiller density for each cultivar (r = 0.454***, n = 72 for All*Star; r = 0.364***, n = 72 for Repell; and r = 0.719***, n = 72 for Barclay). Compared with the other cultivars, Barclay matured 13 –15d later, had the lowest density of fertile tillers (1330 m –2 ), the highest seed dockage (27.9%) and the lowest seed yield (345 kg ha –1 ). All*Star had the highest seed yield (774 kg ha –1 ), the lowest seed dockage (16.7%), and the highest thousand-seed weight (1.55g). Repell was intermediate in seed yield (633 kg ha –1 ) but similar to All*Star, rather than Barclay, in other characteristics. The later maturity, creeping habit and prostrate stature of Barclay may have reduced its ability to produce fertile tillers and seed as efficiently as the other two cultivars at this northern latitude. In the Peace River region, there is ...